Breath figures : mechanisms of multi-scale patterning and strategies for fabrication and applications of microstructured functional porous surfaces /: mechanisms of multi-scale patterning and strategies for fabrication and applications of microstructured functional porous surfaces. ([2020]) - Rodríguez-Hernández, Juan; Bormashenko, Edward
No abstract available